Multiscale agent-based modeling of restenosis after percutaneous transluminal angioplasty: Effects of tissue damage and hemodynamics on cellular activity. (August 2022) - Corti, Anna; Colombo, Monika; Migliavacca, Francesco; Berceli, Scott A.; Casarin, Stefano; Rodriguez Matas, Jose F.; Chiastra, Claudio
Abstract: Background: Restenosis following percutaneous transluminal angioplasty (PTA) in femoral arteries is a major cause of failure of the revascularization procedure. The arterial wall response to PTA is driven by multifactorial, multiscale processes, whose complete understanding is lacking. Multiscale agent-based modeling frameworks, simulating the network of mechanobiological events at cell-tissue scale, can contribute to decipher the pathological pathways of restenosis. In this context, the present study proposes a fully-automated multiscale agent-based modeling framework simulating the arterial wall remodeling due to the wall damage provoked by PTA and to the altered hemodynamics in the post-operative months. Methods: The framework, applied to an idealized femoral artery model, integrated: (i) a PTA module (i.e., structural mechanics simulation), computing the post-PTA arterial morphology and the PTA-induced damage (ii) a hemodynamics module (i.e., computational fluid dynamics simulations), quantifying the near-wall hemodynamics, and (iii) a tissue remodeling module simulating cellular activities through an agent-based model. Results: The framework was able to capture relevant features of the 3-month arterial wall response to PTA, namely (i) the impact of the PTA-induced damage and altered hemodynamics on arterial wall remodeling, including the local intimal growth at the most susceptible regions (i.e., elevated damage levels and low wall shear stress), (ii) the lumen area temporal trend resulting from the interaction of the two inputs, and (iii) a 3-month lumen area restenosis of ∼25%, in accordance with clinical evidence. Conclusions: The overall results demonstrated the framework potentiality in capturing mechanobiological processes underlying restenosis, thus fostering future application to patient-specific scenarios. Highlights: Multiscale agent-based modeling of femoral artery restenosis after angioplasty. Fully automated integration of structural mechanics, CFD and agent-based models. Arterial wall response to PTA-induced damage and hemodynamics post-intervention. The local intimal growth, with regions of focal re-narrowing, was captured. The lumen area temporal trend, featuring different restenosis phases, was captured.